Resilience of Sweet Chestnut and Truffle Holm-Oak Rural Forests in Languedoc-Roussillon, France: Roles of Social-Ecological Legacies, Domestication, and Innovations (Ecology and Society)
The Cvennes sweet chestnut (Castanea sativa Mill.) forest-orchards and the holm-oak (Quercus ilex L.) black truffle (Tuber melanosporum Vittad.) associations of the garrigue in Languedoc-Roussillon have suffered a century of decline because of great reductions of rural populations and lack of understanding of the ecological and social dimensions of these rural forests by sectorial public agencies. Levels of tree and forest domestication alternated during historical periods in parallel with statuses of disorganization and reorganization of local social groups. Social-ecological legacies intrinsically linked to trees, forests, and landscape domestication, as well as knowledge, social, and technical practices have been mobilized and provided a basis for knowledge innovations, new domestications, uses, and new institutional networks related to changes in social set-ups. Collective actions emerging from local needs to revive territories in a modern context, cross-scale and reciprocal exchanges of rural and scientific knowledge, as well as institutional changes are interrelated variables that have enabled innovations and have increased resilience of these rural forests. This paper opens new avenues for future research on the interplay between the effects of social-ecological legacies and innovations on the resilience of social-ecological systems.